Clinical and psychological features of persons with social anxiety disorder associated with traumatic experience - Avramchuk Олександр (Psychosomatic Medicine and General Practice, 2021)
Background. Social anxiety disorder (social phobia) is one of the most common variants of anxiety pathology, which is mainly characterized by a chronic course, persistent symptoms, and a tendency to relapse. Negative social experience in the pathogenesis of social phobia may be accompanied by signs resembling avoidance symptoms, negative alterations in cognition/mood, and changes in arousal and reactivity. In addition, recent scientific studies indicate that individuals with social anxiety disorder suffer from clinically significant symptoms of PTSD in response to social trauma, which impairs quality of life and increases the risk of suicide attempts. Aim. Investigate the clinical and psychological features of people with signs of social anxiety disorder associated with traumatic experiences. Materials and methods. The study group included 179 individuals who complained of significant psychoemotional distress due to avoidance of social interaction and symptoms characteristic of social anxiety disorder with a history of more than six months. The mean age was 31.45 ± 3.84 years, 77.09% (138) were female, 76.5% (137) had higher education, and 26.81% (48) lived alone. As part of the screening of the mental state, we used The MINI: International Neuropsychiatric Interview, self-questionnaires, and scales from complex IAPT were used to study the pathopsychological symptoms, and the Q-LES-Q-SF self-questionnaire was assessed for quality of life. Objective. The study found that individuals who reported significant distress due to avoidance of social interaction were more often diagnosed with social phobia and panic disorder (with and without agoraphobia). They are more characterized by higher levels of psychopathological symptoms, psychosocial dysfunction, and lower subjective satisfaction with the quality of life than the control group. Social avoidance in people with social phobia who have experienced an immediate threat to life was primarily due to comorbid manifestations of post-traumatic symptoms and the impact of traumatic experiences. At the same time, people with social phobia who were affected by social events, defined as traumatic, showed a combination of anxiety and depressive symptoms, which led to distress associated with the avoidance of social interaction. In our opinion, cognitive and behavioral strategies characteristic of the clinical picture of social phobia affect adaptation difficulties, exacerbating distress in daily activities and reducing satisfaction with the quality of life. In addition, for those with a life-threatening experience, the traumatic experience should be considered a separate factor. In contrast, those with a social trauma experienced a modifying factor of vulnerability. The obtained results may lead to different approaches to psychocorrectional work and require further research.